Library Aplication In SDN Klampis Ngasem I Surabaya - Puspitasari, Anita; Setyawan, Henry Bambang; Rahmawati, Endra (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Library is the source of all libraries that exist in an educational institution. This makes the library a benchmark for the quality of an educational institution. With this role, the library becomes the source of all knowledge for students who want to hone their thinking ability to the outside world. Like the current era of globalization rapid development of information technology, so the schools are required to follow the development of information technology in the school library. Library of SDN Klampis Ngasem I Surabaya nowadays, apply the conventional service process that is all the data is still written in the collection and while searching the required data should open the collection's collection, it cause slow in searching data, circulation service or report making. A library also requires a system to collect data, process data, store data, view data and channel good information, one of which is to have high data accuracy. To meet these needs, the business that must be done by the library is the utilization of information technology such as computer along with other library information system application besides the improvement of human resource and system improvement. Kata kunci: Aplication, Library